THE IMPLEMENTATION OF SCIENCE TECHNOLOGY ENGINEERING AND MATHEMATICS (STEM) 5E TO OMPROVE STUDENTS’ CREATIVITY AND PROBLEM-SOLVING SKILLS IN LEARNING THE HUMAN CIRCULATORY SYSTEM - Wawat Septimawati; Anna Fitri Hindriyana; Sulistyono Sulistyono (Universitas Kuningan, 2022)
This research was motivated by the low creativity of students and problem solving skills, only 10% showed indicators of creativity. The purpose of this research is to increase students' creativity and problem solving skills through the implementation of STEM 5E. Creativity and problem solving skills are important for students as provisions in the future. The population in this study were Middle School students. 8 at SMPN 1 Jalaksana, which is divided into two classes, namely the experimental class and the control class. The research design used is a nonequivalent control group design, the type of research is quasi-experimental. The experimental class uses STEM 5E learning, while the control class uses demonstration learning. The instruments used in this study were observation sheets, written tests of 15 description questions with three indicators of problem-solving ability, namely recognizing problems, finding problems, and provide solutions, and other data in the form of a questionnaire to determine student responses. The results of the study on the implementation of STEM 5E learning showed that the preliminary, core and closing activities were carried out well. The results of observations of student creativity showed that the average value of the experimental class was 71.58 while the control class was 28.97. The average result of the experimental class students' problem solving ability was 81.11, much higher than the control class at 40.79. With the implementation of STEM 5E experimental class students are better in terms of creativity and problem solving skills.Keywords: STEM 5E; creativity; ability to solve problems.